AIRLINER CABIN AIR QUALITY - POSSIBLE PROJECTS (Tufts Archival Research Center, 2007)
List of Airline Air Quality Possible Projects including: rechecking flight crews’ "level of hostility" to secondhand smoke, study of lung function in long-term airline employees, locate expert testimony that smoke exposure is not harmful and locate expert testimony that negative effects of denying cigarette to passengers would be overwhelming to crew.